Development and performance of halophilic microalgae-colonized aerobic granular sludge for treating seawater-based wastewater. (September 2020) - Rajitha, K.; Sarvajith, M.; Venugopalan, V.P.; Nancharaiah, Y.V.
Abstract: This study was aimed to evaluate granulation of autochthonous halophilic bacteria and biological nutrient removal under saline conditions. For this, shake-flasks were inoculated with phototrophic biofilm and operated in fill-draw mode under phototrophic and non-phototrophic conditions by feeding seawater-based wastewater. Rapid granulation of autochthonous biofilm microbes was achieved under seawater conditions. Phototrophic biofilm was developed into green coloured microalgae-colonized aerobic granular sludge (AGS) and yellowed-coloured AGS, under phototrophic and non-phototrophic conditions, respectively. Stabilization of sludge volume index (SVI5 ) values at 20 mL/g indicated good granulation (SVI5 /SVI30 ≈ 1). High total nitrogen and phosphate removals of 81–95% and 97%, respectively, were quickly established under saline conditions. Polyphosphate accumulating organisms were detected in the AGS. This study demonstrates rapid granulation of halophilic biomass for quickly establishing nutrient and cultivation of microalgae-colonized AGS for improved harvesting of microalgae. Future research should be aimed to maximize the benefits of microalgae for achieving sustainable wastewater treatment. Graphical abstract: Unlabelled Image Highlights: First report on cultivation of halophilic algal-bacterial granules under saline conditions Use of autochthonous biofilm enabled rapid cultivation of halophilic aerobic granules. Effective total nitrogen and phosphorus removal by halophilic aerobic granular sludge Phosphorus was removed via enhanced biological phosphorus removal mechanism. Nutrient removal pathways were rapidly established using autochthonous microbes.